The Experience of Discursive Problematization of the Axiomatics of Revolution (K.S. Aksakov) - R. A. Alexandrovskii (Дискурс, 2023)
Introduction. This article discusses the ideas about the revolution, the Russian people and the state in the works of Konstantin Sergeevich Aksakov. K.S. Aksakov was a well-known Russian publicist, literary critic, poet and one of the main ideologists of Slavophilism. Over the years, many researchers of Russian philosophy and history have shown interest in his legacy, noting his originality and incredible love for Russia. The purpose of this article is to analyze and highlight the views of Konstantin Aksakov on the revolution - as a reflection on the events that took place in Europe and the Russian Empire during his life and work.Methodology and sources. The results of the study were based on the textual and conceptual analysis of the works of K.S. Aksakov. The main sources were journalistic notes, essays and letters.Results and discussion. Based on the analysis of historical and philosophical sources, the author of the article comes to the conclusion that for a comprehensive analysis and complete understanding of the idea of revolution in the works of K.S. Aksakov, it is necessary to closely study the key concepts of his philosophical views on Russia, the Russian people, the state and their relationship. Conclusion. For K.S. Aksakov's revolution is an exclusively Western phenomenon. The very idea of revolution is extraneous to the Russian people, since the Russian people themselves chose the state for themselves and entered into an equal alliance with it, seeking to protect themselves from any state activity in order to stay in the process of moral and spiritual improvement.